The State of the Art - Psoriatic Arthritis outcome assessment in clinical trials and daily practice - Day, J; Antony, A; Tillett, W; Coates, LC (Elsevier, 2022)
Psoriatic arthritis is a heterogeneous condition with substantial challenges in optimising outcome measures for both clinical trials and daily practice. As with other inflammatory arthritides, there is no gold standard instrument for measuring disease activity or impact, both of which are key to evaluate therapeutic approaches in trials and monitor disease in daily practice. A wide range of domains have been highlighted in the Outcome Measures in Rheumatology (OMERACT) core domain set for psoriatic arthritis; reflecting the disease involvement in multiple tissues (joints, tendons, skin, and spine) and the heterogenous impact of the disease on individuals. This Review summarises the current evidence around outcome measure selection, considering factors such as unidimensional versus multidimensional outcomes, continuous versus binary measures, and the feasibility of these approaches in trials compared with clinical practice.